Screening of two efficient phosphorus-solubilizing bacteria, strain X42 (Bacillus_A_bombysepticus) and strain G62 (Bacillus velezensis) for their ability to promote Gan Nan navel orange growth - Wenyuan Zhao; Tao Peng; Haojie Cao; Huimin Huang; Shuijing Yu (Annals of Microbiology)
Abstract Background Due to inadequacies in the current management practices of navel orange orchards in southern Jiangxi, there is a deficiency in phosphorus content and a decline in overall soil quality. Therefore, developing microbial formulations that increase soil fertility while meeting green ecological standards is highly important. Rhizobacteria promote plant growth through various mechanisms, and given the critical role of phosphorus in plant growth and development, the development and application of such microbial agents offer an effective approach to address the aforementioned issues. Results This study screened two strains of bacteria with high phosphate solubilization capabilities from the roots of navel oranges in southern Jiangxi. These strains were inoculated into potted plants to investigate their potential to promote plant growth. A comparison of the growth indicators of the experimental and control groups, as well as the enzyme activity indicators of navel orange leaves, revealed that both strains exhibited good growth-promoting effects. Furthermore, whole-genome sequencing of the two strains was conducted, and by comparing data from 31 housekeeping genes, strain X42 was preliminarily identified as Bacillus bombysepticus, and strain G62 was identified as Bacillus velezensis. The comparison also revealed the presence of phosphate solubilization-encoding genes in both strains, with strain G62 lacking the genes for phytate mineralization and inorganic phosphorus dissolution, which may prevent it from utilizing additional organic phosphorus sources. Conclusion This study not only confirms the positive impact of two highly efficient phosphate-solubilizing Bacillus strains on the growth of navel oranges in southern Jiangxi but also deepens the understanding of the genetic basis of phosphate-solubilizing traits through whole-genome analysis. These findings are highly important for the development of biofertilizers and their application in sustainable agriculture, especially in terms of improving soil quality and increasing crop yields.